Analisis Input Output Peranan Jasa Angkutan Laut Terhadap Perekonomian Indonesia - Soedomo, R Pramono (Warta Penelitian Perhubungan, 2010)
As a maritime 1U1tian, sea transport sector plmjs an important role in all activities in society, "botheconomic activihJ and other nan-economic acti'zJities. Maritime transport sector plmj a crucial role inprapelling the economy of Indonesin. 711is study is to nnnlyze tile role of marine transportationsenlices to the Indonesinn econorm1 using tlie methodology Input - Output (Model Input - Output).Data used Input - Output Table 2005 17 sectors.The survey results revealed tha.t the actual sea transport services has great potential. and advantagesthat can evolve with the development/ TJOpulation growth. Marine transportation services is thesenlices sector, and therefore has a value of backward linkages of more than one. Meanwhile, the otherhas little value compared to other sectors. As the senJices sector, marine transportation senlices has alarge output multiplier mlue, 1.6844. 711is indicntes tluzt tile multiplier effects of marine transportationservices aztegorized as high.